Eksekusi Objek Jaminan Fidusia oleh Kreditur (Analisis Yuridis Putusan Mahkamah Konstitusi Nomor 18/Puu-Xvii/2019 Tentang Pengujian Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia) - Candera, Ardianto; Mochtar, Dewi Astutty; Indrayanti, Kadek Wiwik; AZ, Mohammad Ghufron (University of Merdeka Malang, 2021)
Â In 2019, the Constitutional Court Decision Number 18 / PUU-XVII / 2019 has been issued which interprets that default cannot be determined unilaterally by creditors. This decision also stipulates that the collateral object cannot be executed directly, even though it has a fiduciary guarantee certificate. The formulation of the problem in writing this thesis is how the executorial power of the fiduciary guarantee object after the Constitutional Court Decision Number 18 / PUU-XVII / 2019 and what are the legal consequences for creditors after the Constitutional Court Decision Number 18 / PUU-XVII / 2019. The research results from the writing of this thesis are that the executorial power on fiduciary guarantees after the issuance of the Constitutional Court Decision Number 18/2019 remains inherent and as strong as a court decision which has permanent legal force, as long as there is an agreement between the debtor as the fiduciary and the creditor as the fiduciary recipient that There has been a breach of contract, and the debtor submits the object of fiduciary security voluntarily and the creditor as the recipient of the fiduciary can still be executed by the creditor as the fiduciary recipient as long as it has been promised from the beginning regarding the default clause.